Downward Trend in Pediatric Resident Laryngoscopy Participation in PICUs. Issue 5 (May 2018) - Gabrani, Aayush; Kojima, Taiki; Sanders, Ronald C.; Shenoi, Asha; Montgomery, Vicki; Parsons, Simon J.; Gangadharan, Sandeep; Nett, Sholeen; Napolitano, Natalie; Tarquinio, Keiko; Simon, Dennis W.; Lee, Anthony; et al.
Abstract : Objectives: As of July 2013, pediatric resident trainee guidelines in the United States no longer require proficiency in nonneonatal tracheal intubation. We hypothesized that laryngoscopy by pediatric residents has decreased over time, with a more pronounced decrease after this guideline change. Design: Prospective cohort study. Setting: Twenty-five PICUs at various children's hospitals across the United States. Patients: Tracheal intubations performed in PICUs from July 2010 to June 2016 in the multicenter tracheal intubation database (National Emergency Airway Registry for Children). Intervention: None. Measurements and Main Results: Prospective cohort study in which all primary tracheal intubations occurring in the United States from July 2010 to June 2016 in the multicenter tracheal intubation database (National Emergency Airway Registry for Children) were analyzed. Participating PICU leaders were also asked to describe their local airway management training for residents. Resident participation trends over time, stratified by presence of a Pediatric Critical Care Medicine fellowship and airway training curriculum for residents, were described. A total of 9, 203 tracheal intubations from 25 PICUs were reported. Pediatric residents participated in 16% of tracheal intubations as first laryngoscopists: 14% in PICUs with a Pediatric Critical Care Medicine fellowship and 34% in PICUs without one ( p < 0.001). Resident participation decreased significantly over time (3.4% per year; p < 0.001). The decrease was significant in ICUs with a Pediatric Critical Care Medicine fellowship ( p < 0.001) but not in ICUs without one ( p = 0.73). After adjusting for site-level clustering, patient characteristics, and Pediatric Critical Care Medicine fellowship presence, the Accreditation Council for Graduate Medical Education guideline change was not associated with lower participation by residents (odds ratio, 0.86; 95% CI, 0.59–1.24; p = 0.43). The downward trend of resident participation was similar regardless of the presence of an airway curriculum for residents. Conclusion: Laryngoscopy by pediatric residents has substantially decreased over time. This downward trend was not associated with the 2013 Accreditation Council for Graduate Medical Education change in residency requirements. Abstract : Supplemental Digital Content is available in the text.